2023
DOI: 10.1111/jsap.13654
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic measurement of caudal vena cava to aorta ratio during fluid resuscitation of dogs with spontaneous circulatory shock

Abstract: ObjectivesTo describe the change in the caudal vena cava to aorta ratio (CVC:Ao) ratio during fluid resuscitation of circulatory shock in dogs and compare these results with those of the physical examination and blood lactate.Materials and MethodsPerfusion parameters and blood lactate were recorded at admission. An abdominal point‐of‐care ultrasound protocol was performed, during which the caudal vena cava to aorta ratio was measured on the spleno‐renal view. Measurements were performed within 5 minutes before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…In previous reports, the CVC/Ao value was reported to range between 0.9 and 1.32 in healthy dogs. 2,14 In human medicine, it was reported that the diameter of the aorta remains stable during severe hypovolemic shock or dehydration compared with the decrease in the diameter of the inferior vena cava (IVC). 20 However, as previously reported, 11 a decrease in several ultrasonographic CVC/Ao, corresponding to the IVC/Ao in human studies can be observed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous reports, the CVC/Ao value was reported to range between 0.9 and 1.32 in healthy dogs. 2,14 In human medicine, it was reported that the diameter of the aorta remains stable during severe hypovolemic shock or dehydration compared with the decrease in the diameter of the inferior vena cava (IVC). 20 However, as previously reported, 11 a decrease in several ultrasonographic CVC/Ao, corresponding to the IVC/Ao in human studies can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has been reported that CVC/Ao decreased and reached the reference range 30 min after administration of furosemide at a dose of 2 mg/kg intravenous to eight dogs with hypervolemia due to congestive heart failure. 14 In addition, another study evaluated the correlation between serum lactate concentration and CVC/Ao before and after fluid therapy in 17 dogs with naturally occurring hypovolemic shock. It was reported that there was a significant increase in CVC/Ao values after fluid replacement and no change in lactate levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations